2012
DOI: 10.1029/2011ja017441
|View full text |Cite
|
Sign up to set email alerts
|

Dipole tilt control of the magnetopause for southward IMF from global magnetohydrodynamic simulations

Abstract: [1] Numerical results from a physics-based global magnetohydrodynamic (MHD) model are used to examine the effect of the dipole tilt angle (y) on the location and shape of the magnetopause. Identification of the magnetopause location in the simulation domain is automated using criteria based on the current density and the shape of the streamlines. These data are fitted with a three-dimensional surface controlled by 10 configuration parameters which allow description of the cusp geometry as well as the asymmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 52 publications
1
54
0
Order By: Relevance
“…By finding approximately the solar wind streamlines encompassing the inner edge of the void, Palmroth et al [2003] developed an automated technique for identifying the magnetopause surface from the simulations. Recently, Liu et al [2012] indicated that the streamline method is not able to determine the subsolar point very well, and they used the peaks of the current density to identify the subsolar magnetopause instead. In this study, we make a slight modification of the streamline method as Liu et al [2012] did.…”
Section: Diagnosis Methods For the Magnetopause Locationmentioning
confidence: 99%
See 2 more Smart Citations
“…By finding approximately the solar wind streamlines encompassing the inner edge of the void, Palmroth et al [2003] developed an automated technique for identifying the magnetopause surface from the simulations. Recently, Liu et al [2012] indicated that the streamline method is not able to determine the subsolar point very well, and they used the peaks of the current density to identify the subsolar magnetopause instead. In this study, we make a slight modification of the streamline method as Liu et al [2012] did.…”
Section: Diagnosis Methods For the Magnetopause Locationmentioning
confidence: 99%
“…Recently, Liu et al [2012] indicated that the streamline method is not able to determine the subsolar point very well, and they used the peaks of the current density to identify the subsolar magnetopause instead. In this study, we make a slight modification of the streamline method as Liu et al [2012] did.…”
Section: Diagnosis Methods For the Magnetopause Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that the solar wind dynamic pressure can affect the magnetopause size, while the shape of the magnetopause is controlled by the IMF B z (e.g., Shue et al, 1997;Lu et al, 2011;Boardsen et al, 2000). Later work has further indicated that the dipole tilt angle can also affect the magnetopause shape (e.g., Liu et al, 2012). Our work has indicated that the IMF cone angle might be another important parameter that can affect the magnetopause shape.…”
Section: Discussionmentioning
confidence: 78%
“…The latter fact indicates that the dipole tilt effect is not fully represented by the Boardsen00 model. Previous work has shown that the dipole tilt angle has few effects on the equatorial magnetopause but has great effects on the high-latitude magnetopause (Lin et al, 2010;Liu et al, 2012;Boardsen et al, 2000). As the dipole tilt angle becomes more negative, the high-latitude magnetopause is displaced inwards in the Northern Hemisphere, while in the Southern Hemisphere the magnetopause is displaced outward (Boardsen et al, 2000).…”
Section: Discussionmentioning
confidence: 94%